The Light Triad of Personality, Emotional Intelligence and Satisfaction With Life in Adulthood - Jankiewicz, Anna; Michałek-Kwiecień, Justyna (Przegląd Psychologiczny, 2024)
Objective: The study aimed to determine the relationship between the personality traits included in the light triad scale (faith in humanity, humanism, kantianism) and emotional intelligence and to examine how these variables are related to life satisfaction in people during adulthood. Method: The study was conducted in a group of 162 people between 18 and 85. The scales used were the Light triad scale in the Polish adaptation by Gerymski and Krok (2019), the INTE Questionnaire by Schutte and colleagues (1998) in the Polish adaptation by Ciechanowicz, Jaworowska and Matczak (2000), and the SWLS (Satisfaction With Life Scale) by Diener, Emmons, Larson, and Griffin (1985) in a Polish adaptation by Juczyński (2001). Results: The results indicate statistically significant positive relationships between the light triad traits, emotional intelligence, and life satisfaction. The only trait that is not correlated with life satisfaction is kantianism. There was also a positive correlation between emotional intelligence and all traits of the light triad. Gender differentiated the studied group regarding emotional intelligence and the traits of the light triad – women achieved a higher emotional intelligence index, higher humanism, and an overall score of light triad traits. There was a positive relationship between the age of the studied group and the overall index of light triad traits. The study also found that emotional intelligence and light triad traits explain 23% of the variance in life satisfaction. Conclusions: The study provided important findings on the light triad personality traits, which are relatively new and still developing constructs. It has added to the existing pool of research on the relationship with emotional intelligence. Emotional intelligence and the light triad, as opposed to dark triad traits, are associated with higher life satisfaction.